The Effect of a Local Injection of Flurbiprofen Ester Microspheres on Systemic Inflammatory Model Rats With a Closed Femoral Shaft Fracture - Peng, Hui-Ming; Xiao, Ke; Zhu, Wei; Wang, Ying-Jie; Bian, Yan-Yan; Wang, Wei; Qian, Wen-Wei; Weng, Xi-Sheng (Frontiers in Pharmacology, 2022)
Background: Periarticular injections with a combination of local anesthetics, non-steroidal anti-inflammatory analgesics (NSAIDs), and epinephrine are becoming increasingly popular in the perioperative analgesia of artificial joint replacement. However, data on the efficacy and safety of local injection NSAIDs are still scarce. The purpose of this study was to investigate the efficacy and safety of a local injection of Flurbiprofen Ester Lipid microspheres into the inflammatory model of femoral shaft closed fractures in rats. Methods: A systemic inflammatory model was induced in SD rats (60) by closed femoral shaft fracture; 12 non-fractured rats were used as the blank control group (group A). The systemic inflammation model of 60 rats was divided into 5 groups (12 in each group); Group B: intramuscular injectionof the same amount of normal saline at different time points as a negative control; Group C: intravenous injection of Flurbiprofen Ester microspheres (4.5 mg/kg) at different time points; Group D: intramuscular injection of Flurbiprofen Ester microspheres (2.25 mg/kg) at different time points; Group E: intramuscular injection of Flurbiprofen Ester microspheres (4.5 mg/kg) at different time points; Group F: intramuscular injection of Flurbiprofen Ester microspheres (9 mg/kg) at different time points. The behavioral test observed the behavior of the rats. Then, the inflammation factors of CRP, IL-6, COX-1, COX-2 and TNF-αby ELISA were recorded. Results: Through the behavioral test it could be found that the effect of the intramuscular and intravenous injections of Flurbiprofen Ester microspheres was similar. Fracture rats with a local injection of Flurbiprofen Ester microspheres showed lower inflammation levels measured by COX-1, CRP, and TNF-α compared with the control group. Pathological sections at 24h, 48h, and 96h after surgery did not display any local muscle necrosis at the local injection site. These findings suggested that a Flurbiprofen Ester microsphere muscular injection exhibited a similar effect to an intravenous injection. Conclusions: The local injection of Flurbiprofen Ester microspheres significantly reduced the inflammatory response in fracture rats and did not increase the risk of muscle necrosis, suggesting its feasibility in local injection analgesia.